Individualization and self-design technology implementation results for continuing education of teachers - Petrova, М.V.Kotov, S.V., Petrova, N.P.; N.SKotovа; S.A., Borlakova (Opción, 2020)
The article presents the results of the study that determines the effectiveness of continuing education of teachers based on continuing education programs that use the idea of individualization and self-design technology via the analysis of scientific and pedagogical literature on the topic of research and pedagogical modeling. As a result, the majority of teachers from the experimental group (84.0%) are satisfied with the results of their training, which is 32% more than the share of teachers in the control group. In conclusion, self-designing is directly related to the processes of self-improvement, self-actualization, self-esteem, expanding the idea of self-designing phenomenon.